The Symbolic Meaning of Marriage Taboo in Purbalingga and Banyumas Villages - Sugeng Priyadi (Proceedings Series on Social Sciences & Humanities, 2023)
The marriage taboo in the rural community of Purbalingga and Banyumas illustrates the phenomenon of socio-cultural plurality which is based on socio-political legitimacy. The emergence of marriage taboos is caused by social conflicts as the manifestation of incest marriage, social rivalry, and legitimacy battle. In those conflicts, the communities of Onje, Banjaranyar, and Raden Kaligenteng are the troublemakers. In addition, the communities of Sambeng Kulon, Sambeng Wetan, Jompo Kulon, and Jompo Wetan can also be categorized as the troublemakers since they are involved in the internal conflict which made them separated into parts. Those marriage taboos indicate something that can be understood as the shift of cosmos into chaos. The chaotic situation, however, is more dominant because the shift has not resulted in a new cosmos so that it is always in the liminal or threshold position. The position can be explained clearly in terms of relative binary opposition featuring a third party which takes the liminal position.